A Hierarchy-of-Effects Approach to Designing a Social Marketing Game. Issue 2 (2nd April 2016) - Russell-Bennett, Rebekah; Leo, Cheryl; Rundle-Thiele, Sharyn; Drennan, Judy
ABSTRACT: While there is great enthusiasm and interest by social marketers for games as a social marketing intervention, there is little evidence of the impact of these games. This research seeks to fill this gap by testing a theoretical model based on the experiential hierarchy of effects. An online game about the physiological effects of drinking was designed for high-school students and implemented in an educational curriculum with 223 participants (96% response rate) completing an online survey. The data was analyzed using structural equation modeling (SEM) and showed support for nine of the eleven hypotheses. The results show game characteristics of enjoyment (feel), knowledge (learn), and challenge (do) significantly related to attitudes and moderate-drinking behavioral intentions, ability to control drinking, and awareness of the physical consequences of drinking. There were no gender differences.